Enkehøj – En boplads med klokkebægerkeramik og korn - Møbjerg, Tinna; Jensen, Peter Mose; Mikkelsen, Peter Hambro (Kuml, 2007)
Enkehøj A settlement with Bell Beaker pottery and charred grain Three settlements from Late Neolithic times have been excavated within Herning Museum’s area of archaeological responsibility since 2004 Enkehøj, Sjællandsvej og Gilmosevej (fig. 1). At Enkehøj, several pits containing carbonised grain were found, as well as the remains of at least two two-aisled houses, one of which had a sunken floor (figs. 2 and 6). In addition to this, a thin culture layer was documented in the northeastern part of the excavation area which contained flint tools, including a fragment of a pressure-flaked dagger that had been re-used as a burin (fig. 3). Pit 37 contained about 200 ml of grain as well as several un-ornamented potsherds and a Bell Beaker-like vessel (fig. 4). Pit 288 did not have any carbonised grain but contained potsherds which date the pit to the Single Grave culture’s Bottom Grave period (fig. 5). Pits 304 and 327 probably formed parts of the construction of house 240 (fig. 6). Both the pits and the house contained carbonised grain. Furthermore, a polished flint axe with an outwardly flared edge was recovered, together with a large curved beaker and a small miniature pottery vessel (fig. 7). The sherds belonging to the large beaker were found scattered through the fill of both pit 304 and pit 327. The floor layer of house 240 contained very few potsherds, a fragment of a quernstone and a perforated axe (fig. 8). Below the sunken floor there was also a small pit containing processed grain. Pit 708 was located in the northern part of the investigated area. It contained almost 3.5 l of processed grain, sherds from several ornamented pottery vessels and a small, straight-walled beaker filled with grain (figs. 9-10). On the basis of the Bell Beaker-like vessel, the pits and the houses were dated to the early part of the Late Neolithic, 2400-2200 BC. The radiocarbon dates for carbonized barley grains are, however, more than 200 years later (table 1). This may be due to a delay in the Bell Beaker culture’s influence in the Central Jutish area relative to Northern Jutland with its rich flint deposits. The Late Neolithic grain from Enkehøj is the first large find in the Herning area of crop remains from the end of the Neolithic. The grain samples, comprising in total more than 16 l of processed grain, were collected from pits and postholes from the roof-bearing posts of two Late Neolithic longhouses. One of them, house 240, had a central depression, while the other, house 480, did not. In addition to the samples from the two houses, samples were also taken from three outdoor pits (pits 25, 37 and 708) on the site (fig. 11). Naked barley dominates in most of the samples but a quantity of emmer was also identified (fig. 12.2). Spelt was present in such small amounts that cultivation of this type cannot be established with certainty. Spelt was, however, cultivated in the area. This is apparent from the find from Gilmosevej where large amounts of carbonised acorns were found in addition to a quantity of naked barley and spelt (fig. 16). This distribution of crop types from Enkehøj is in good agreement with the general picture of Danish agriculture extending from the Late Neolithic into the Bronze Age (see table 2). The occurrence of large quantities of carbonised plant remains at Enkehøj gives a broader impression of Late Neolithic agriculture than that normally available from archaeological finds. Archaeobotanical analysis of carbonised plant remains can reveal how arable fields were cultivated in practice. This can be done by comparing the relative abundance of grain, chaff and weed seeds. Differences in the frequency can be linked to differences in the treatment of the crops, both before, during and after harvest. However, it must be emphasised that a prehistoric arable field cannot be compared with either historical or modern fields which had/have much more uniform conditions (fig. 13). Weeds appear only sporadically among the Enkehøj grain; the absence of weeds, together with the deficiency in the amount of chaff, straw etc., shows that the grain had been processed, i.e. threshed and cleaned. But the presence of seeds of various different species of knotgrass does reveal the height at which the Enkehøj cereals were harvested (fig. 14). The numbers of glume bases and grains of emmer are fairly similar. In contrast, there are virtually no barley rachis segments relative to the number of barley grains. This shows that emmer had been stored in the form of spikelets while the barley was stored as naked processed grains (fig. 15). This corresponds to earlier Danish investigations from this period, indicating that the glumes which, in the case of emmer, sit relatively firmly around the grains, were not removed from the grain until the latter was taken indoors, immediately before cooking. As the process of removing the glumes may have a negative effect on the grain’s subsequent germination capacity, and as the glumes also protect the grain against vermin and humidity, there are several good reasons for storing emmer in this particular way. With regard to doubts about finds of stored grain from outdoor pits there are several examples of grain being stored in two-aisled longhouses from the Late Neolithic and the Early Bronze Age, both in houses with and without a sunken floor, as seen in the two houses at Enkehøj. Indications of storage are apparent at several places in houses, particularly in the eastern parts and in sunken areas. There is an example of grain storage in wooden containers below floor level from Petersborg West near Østbirk. A possible reason for the sunken areas in the two-aisled houses may have been to increase the free height below the roof and, thereby, the available storage capacity in certain areas within the houses. By constructing a floor above the sunken area it would have been possible to store crops both at and below floor level. However, the floors in the sunken areas were workplaces, indicating that there were ceilings here or storage on lofts under the roof in this part. A recently-excavated house site at Dalsgaard II has indented posts in the sunken part of the house – these may have supported a loft construction (fig. 17). Different types of crops were probably stored in different places. For example, seed corn may have been stored at or below floor level, as the constant smoke under the roof would have had a destructive effect on the subsequent germination capacities of the grain. Changes in crops during the Late Neolithic and adjacent periods are shown in table 2. A clear difference can be seen between the crop composition in the Late Neolithic and in the Early Bronze Age. Samples from the letter are characterised by naked barley, emmer and, in part, spelt, compared to the Single Grave period when naked barley clearly dominates relative to all other cereal/crop types. There are also features of the tools from the Single Grave period indicating the great importance of barley in this particular period. For example, Helle Juel Jensen has distinguished two types of blade sickle in period V of the Late Funnel Beaker culture and in the Single Grave period on the basis of different wear traces. One type of blade sickle normally has wear traces indicating the cutting the cereals low on the straw. The other type, in contrast, normally functioned as a tool to severe the ears from the straw (fig. 18). The transition to the cultivation of a larger number of cereal types may have been prompted by several factors. It has, for example, been suggested that there was a move towards the cultivation of more fertile areas in the Late Neolithic. As naked barley is a less demanding crop than wheat it is also possible that the increased cultivation of wheat characterises the beginning of systematic manuring. The earliest evidence of manuring in Denmark is from the Late Bronze Age at Bjerge in Thy, in an area where naked barley and emmer were cultivated, as was also the case at Enkehøj. Future investigations will hopefully reveal whether improvement of the soil in this way was a usual part of agriculture as early as the Late Neolithic. Tinna Møbjerg Herning Museum Peter Mose Jensen Peter Hambro Mikkelsen Moesgård Museum